Vaccination against hepatitis A and B in patients with chronic liver disease and type 2 diabetes: has anything changed?. (2nd June 2016) - Koenig, Aaron; Stepanova, Maria; Felix, Sean; Kalwaney, Shirley; Clement, Stephen; Younossi, Zobair M.
Abstract: Background & Aims: Given the severity of acute hepatitis in patients with chronic liver diseases (CLD) and patients with type 2 diabetes (DM), most of these patients are recommended to be vaccinated. The aim is to assess the recent changes in HAV and HBV vaccination rates in patients with CLD and DM in the U.S. using the most recent population data. Methods: We used the National Health and Nutrition Examination Surveys (NHANES) cycles 2009–2012 and 2013–2014, and compared those to previous cycles (1999–2004 and 2005–2008). Results: In general U.S. population, the rates of quality measure (QM, serologic immunity or history of vaccination) for HBV increased from 31.9% in 1999–2004 to 49.5% in 2013–2014 ( P < 0.0001), synchronously with an increase in self‐reported HBV vaccination: from 24.4% to 41.3% ( P < 0.0001). A similar increase was noted for HAV: 12.0% in 1999–2004 to 33.4% in 2013–2014 in vaccination, 44.0% to 52.4% in HAV QM (all P < 0.0001). Greater recent increases in HBV QM were noted in non‐HBV CLD patients: 34.7% to 56.8% in HBV QM and 22.7% to 51.1% in HBV vaccination (all P < 0.0001), while the changes in patients with diabetes were similar to those in general U.S. population despite the recent CDC recommendation (for the age 19–59): 31.0% to 45.1% ( P = 0.007) in HBV QM, and 22.3% to 39.0% ( P = 0.0004) in HBV vaccination. Conclusions: Despite recommendations, HAV and HBV vaccination rates in patients with CLD and DM remain relatively low. Better vaccination strategies for these high risk patients should be undertaken.